UNVEILING THE ROLES OF SUNAN AMPEL IN THE NUSANTARA: AN ENGAGING HISTORICAL PERSPECTIVE - Azizah, Iffah Nur; Yusuf, Hilmy Himawan; Wasid (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
History is not just about the past, but it carries a diverse array of human cultural practices that continue to shape contemporary culture. This awareness makes historical approaches crucial for advancing human cultural processes from material progress to the formation of non-material components, such as culture, ethics, and morality. In this context, it is necessary to reexamine Sunan Ampel’s role in preaching on the island of Java in the 14th century created a breakthrough by combining local culture with the educational concepts he taught. The philosophy of Moh-Limo, which is known as Sunan Ampel’s teaching, is one of the many wisdoms of Sunan Ampel in educating his community. The application of Moh-Limo’s is considered successful in improving moral conditions during that era, when moral decay was seen as a cause of the downfall of The Majapahit era. This writing will focus on discussing Sunan Ampel’s efforts to educate morality with Moh- Limo’s teachings, as well as contextualizing Moh-Limo’s philosophy in contemporary contexts amidst the poor state of morality in society. To elaborate on this, the writers uses functionalism theory. This theory emphasizes the importance of understanding how every aspect of culture and society has a function in maintaining balance and the sustainability of society. The approach used in this writing is historical theory, biographical, and social-cultural. The results of this research show that education during Sunan Ampel’s era, which implemented Moh-Limo and established pesantren as a center of religious education, is considered capable of producing strong leaders who have an impact on the process of Islamization in Nusantara